Thulium laser enucleation of the prostate (ThuLEP): Results, complications, and risk factors in 139 consecutive cases - Marco Raber (Taylor & Francis Group, 2018)
Objectives: To report our experience with the emerging technique of thulium laser enucleation of the prostate (ThuLEP) for the treatment for prostate hyperplasia. Patients and methods: Our inclusion criteria were an International Prostate Symptom Score (IPSS) of >15 and a quality-of-life (QoL) score of >3 in patients with confirmed bladder outflow obstruction, no longer responsive to medical therapy, with a significant post-void residual urine volume (PVR; >100 mL), with or without recurrent urinary tract infection and/or acute urinary retention. Patients with neurogenic bladder, urethral strictures, bladder stones, and previously failed transurethral prostate surgery were excluded. Results: In all, 139 men were included in the study. The mean age was 67.8 years. The IPSS and QoL score improved by 17.6 and 2.6, respectively. The flow rate increased from a mean of 9.6 mL to 31.2 mL and the PVR decreased from a mean of 131 mL to 30 mL. On univariate and multivariate analyses, operating time was a predictive factor for haemoglobin drop during the operation. Heparin prophylaxis was the only risk factor identified for postoperative bleeding. Two patients (0.01%) required blood transfusion. One patient (0.007%) required re-intervention for bleeding control, and two patients developed urethral and bladder neck strictures (0.01%). Conclusion: ThuLEP is safe and reproducible. Whilst it significantly reduces intraoperative bleeding as compared to transurethral resection of the prostate, operating time and perioperative heparin prophylaxis may still lead to a Hb drop and constitute a risk factor for postoperative bleeding. Therefore, a potential risk of deep vein thrombosis requiring heparin prophylaxis should be carefully considered and balanced with the expected clinical benefit of the operation. Keywords: Prostate enlargement, Thulium laser, Endoscopy, Treatment